Effect of dipolar interaction on magnetic properties of magnetite nanoparticles system: a simulation study - Nguyen, Hoang Thanh; Lan, T. N.; N. M., Tuan (Communications in Physics, 2023)
Superparamagnetic iron oxide nanoparticles are a potential candidate for novel research. The inter-particle interactions play a signiﬁcant role in determining the overall magnetic behavior of a magnetic nanoparticle assembly, especially in dipolar interaction. In this paper, we have synthesized a practical sample and then applied an atomistic spin model simulation study with input parameters obtained from experimental measurements to investigate the influence of the dipolar interaction on the magnetic properties of Fe3O4 magnetite nanoparticles.